2021
DOI: 10.18071/isz.74.0273
|View full text |Cite
|
Sign up to set email alerts
|

Acute transverse myelitis after inactivated COVID-19 vaccine

Abstract: Vaccines against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been rapidly developed to prevent coronavirus disease 2019 (COVID-19) pandemic. There is increasing safety concerns regarding COVID-19 vaccines. We report a 78-year old woman who was presented with tetraparesis, paresthesias of bilateral upper extremities, and urinary retention of one-day duration. Three weeks before these symptoms, she was vaccinated with CoronaVAC vaccine (Sinovac Life Sciences, China). Spine magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…[ 2 ] Recently, several cases of transverse myelitis from 1 to 14 days after COVID-19 vaccination have been also reported. [ 3 9 ] A single case of transverse myelitis following the mRNA-1273 COVID-19 vaccine was recently reported by Khan et al [ 8 ] Notably, the present case showed several differences from the previous case, including:…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…[ 2 ] Recently, several cases of transverse myelitis from 1 to 14 days after COVID-19 vaccination have been also reported. [ 3 9 ] A single case of transverse myelitis following the mRNA-1273 COVID-19 vaccine was recently reported by Khan et al [ 8 ] Notably, the present case showed several differences from the previous case, including:…”
Section: Discussionmentioning
confidence: 62%
“…Recently, several cases of transverse myelitis from 1 to 14 days after COVID-19 vaccination have been also reported. [ 3 9 ] Here we report a rare case presenting with transverse myelitis following COVID-19 vaccination with mRNA-1273, Moderna.…”
Section: Introductionmentioning
confidence: 98%
“…For COVID-19 vaccine-related events, a total of 51,755,447 doses of COVID-19 vaccines were administered until March 2021 and nine cases of related ATM were reported among 9442 adverse events; the incidence is approximately 1.739/per million people [ 2 ]. After the literature review, we summarized the published case reports of SARS-CoV-2 vaccination-related transverse myelitis with detailed clinical information in Table 1 [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The swelling and pain was reported to be resolved 2 days post treatment and at follow--up one month later, the condition of the joint was found to be normal (62). A 78--year old woman presented for treatment with tetraparesis, paresthesias of bilateral upper extremities, and urinary retention of one--day duration (63). Three weeks before symptom onset, the patient had been vaccinated with CoronaVac (63).…”
Section: (33) Inactivated-virus Sars-cov-2 Vaccine Candidatesmentioning
confidence: 99%
“…A 78--year old woman presented for treatment with tetraparesis, paresthesias of bilateral upper extremities, and urinary retention of one--day duration (63). Three weeks before symptom onset, the patient had been vaccinated with CoronaVac (63). Spine magnetic resonance imaging showed longitudinally extensive transverse myelitis (TM) from the C1 to the T3 spinal cord segment (63).…”
Section: (33) Inactivated-virus Sars-cov-2 Vaccine Candidatesmentioning
confidence: 99%